The Center for Research and Training in Public Administration of Costa Rica as a producer of knowledge and scientific trends - Montero Corrales, Carlos Alberto (Universidad Nacional del Litoral, 2021)
The Center for Research and Training in Public Administration (CICAP) of the University of Costa Rica (UCR) is an institution that, for 49 years, functioned as a vehicle for the diffusion of the field of knowledge of Public Administration in the country. Given its importance in generating and disseminating knowledge to improve public management capacity, we present a characterization of the scientific production of the Center, basing the discussion on two questions: How can evidence-based decisions be made to publish and disseminate scientific production in Public Administration at an international level? In what way does CICAP's scientific production results in input for decision-making with greater scientific impact on this field research? For this, we employ a mixed methodology based on a bibliometric study and switch. As a result, it is possible to identify both the dynamics of the production of knowledge of the CICAP, as well as potential lines of research in the field of Public Administration: Municipal Development, Public Administration, Customs and Foreign Trade and Open Government. Therefore, the article offers an empirical contribution to CICAP and a theoretical contribution to the field of Public Administration.